2010
DOI: 10.1038/mt.2010.85
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of RNAi Therapeutics With Endogenous and Exogenous Ligand-Based Mechanisms

Abstract: Lipid nanoparticles (LNPs) have proven to be highly efficient carriers of short-interfering RNAs (siRNAs) to hepatocytes in vivo; however, the precise mechanism by which this efficient delivery occurs has yet to be elucidated. We found that apolipoprotein E (apoE), which plays a major role in the clearance and hepatocellular uptake of physiological lipoproteins, also acts as an endogenous targeting ligand for ionizable LNPs (iLNPs), but not cationic LNPs (cLNPs). The role of apoE was investigated using both in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
777
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 918 publications
(835 citation statements)
references
References 30 publications
19
777
2
4
Order By: Relevance
“…The FVII model was primarily chosen for this evaluation because previous work from our laboratory and others have demonstrated that ionizable LNPs, similar to those prepared in this work, target liver hepatocytes presumably due to interactions with endogenous lipoproteins (25). All 32 members of the lipid library were formulated into LNPs with siRNA against FVII and administered i.v.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FVII model was primarily chosen for this evaluation because previous work from our laboratory and others have demonstrated that ionizable LNPs, similar to those prepared in this work, target liver hepatocytes presumably due to interactions with endogenous lipoproteins (25). All 32 members of the lipid library were formulated into LNPs with siRNA against FVII and administered i.v.…”
Section: Resultsmentioning
confidence: 99%
“…LNPs were used in this study because they have been shown to facilitate efficient delivery to hepatic and immune targets (23,(25)(26)(27). In the past few years, LNPs formulated with siRNAs against transthyretin (TTR) and proprotein convertase subtilisin/kexin type 9 (PCSK9) in rodents and nonhuman primates have produced promising preclinical results and several clinical trials involving LNPs are currently underway (28)(29)(30).…”
mentioning
confidence: 99%
“…To identify a potent Alas1-siRNA, a panel of siRNAs targeting Alas1 was initially screened for their ability to inhibit Alas1 mRNA expression in cultured hepatic cells. The most active compounds were formulated into lipid nanoparticles (LNPs) for efficient hepatic delivery (21)(22)(23) and evaluated for their ability to down-regulate hepatic Alas1 mRNA expression in wild-type mice. The selected Alas1-siRNA was then evaluated in the mouse model for AIP for its effectiveness to prevent or treat an induced acute attack.…”
Section: Significancementioning
confidence: 99%
“…The endocytosis of LNP-siRNA systems containing ionizable cationic lipids is dependent on association with apolipoprotein E (ApoE) and proceeds by the classic clathrin-mediated endocytosis mechanism used for uptake of cholesterol-containing LDL. 20 However, it has been noted that low NPC1 levels result in reduced internalization and lower transfection efficiencies for a polymer-based gene delivery system which enters cells primarily through caveolaemediated endocytosis. 21 Thus, the benefits of NP3.47 on LNPsiRNA intracellular accumulation and gene silencing potencies may depend on the particular endocytotic mechanism employed.…”
Section: Discussionmentioning
confidence: 99%